Investigating the interactions between dyes and porous/composite materials: A comprehensive study - Muhammad Zeeshan; Tariq Javed; Chandresh Kumari; Anusha Thumma; Muhammad Wasim; Muhammad Babar Taj; Ishu Sharma; Muhammad Nouman Haider; Maryam Batool (Sustainable Chemistry for the Environment)
The subject of pollution resulting from dyes has emerged as a significant global issue. Dyes adsorption analysis has gained more significance in the last several years. The process of adsorption are among the most financially viable and effective approaches for reducing dye concentrations in water systems. These hazardous and carcinogenic dyes find their way into water sources through the discharge from numerous sectors like textiles, paints, cosmetics, paper etc. This investigation has delivered an extensive overview of numerous dyes, detailing their adverse effects on human health as well as aquatic organisms. The comprehensive analysis presented in this review encompasses dyes' adsorption on a variety of surfaces, including porous polymers, carbon and clay based materials, layered double hydroxides (LDH), bio-sorbents and metal-organic frameworks (MOF). Comprehensive analysis has been conducted on the structures of these materials as well as the essential functional groups that drive dye adsorption. Additionally, various factors influencing the rate of adsorption are underscored. A brief discussion on the economic aspect is also included. Various mechanisms for dyes removal and theoretical calculations are also discussed. Readers stand to benefit significantly from this review as it offers a thorough exploration of all facets of dye adsorption. Furthermore, the review essay has touched upon the constraints and potential opportunities in this field.